In West and Central Africa, authorities must fight corruption and uphold the human rights of those who expose it - Amnesty International (Amnesty International, 2023)
West and Central African states must stop persecuting human rights defenders who expose corruption, bribery and abuse of office, and instead take concrete and effective measures to protect and support them, Amnesty International said today, in observing African Anti-Corruption Day. Today marks the 20th anniversary of the African Union Convention on Preventing and Combating Corruption.
Africa
Keywords: 2023-07 July; Human Rights Defenders; Middle Africa; Western Africa